Potensi dan Kesesuaian Lahan Budidaya Rumput Laut (Kappaphycus alvarezii) Di Sekitar Perairan Kabupaten Wakatobi Provinsi Sulawesi Tenggara [Potential And Suitability Of Land Seaweed Farming (Kappaphycus alvarezii) Water Around The District Wakatobi Southeast Sulawesi] - Mudian Paena; Nur Ansari Rangka (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract Ragulasi government of commodities in the field of aquaculture developed into a major trigger of the mushrooming development of seaweed farming. (Kappaphycus alvarezii) in most coastal areas in Indonesia, not least in district Wakatobi Southeast Sulawesi. In development, the local government in this case the relevant agencies do not yet have data on potential and suitability of the land to be used as a reference in determining the development strategy. Based on this research has been done to calculate the potential and aimed to determine the suitability of land for seaweed cultivation in the district of Wakatobi. The study was conducted with the direct survey method to extract the characteristics of the study sites for hydro-oceanographic dynamics which is closely linked with the growth of seaweed. Data were tabulated and the field measurement results were analyzed descriptively, whereas spatial analysis for thematic map creation and distribution of the potential suitability of land is done by applying the technology of geographic information systems (GIS) utilizing software Arc-View 3.3. The results showed that the distribution characteristics of hydro-dynamics-osenaografi around Wakatobi waters are bersubstrat sand, coral sand and coral; flow rate between 0.011 to 0.07 m / sec; brightness from 2.5 to 15 meters; depth of 2.5 to 13.7 meters; temperature of 29.42 to 30.2 ° C; pH 7.58 to 8.23; salinity 34.95 to 36.88 ppt; okesigen dissolved from 6.06 to 6.25 m / L; total organic matter (BOT) from 35.52 to 42.6 mg / L; ammonia (NH3) from 0.0096 to 0.0136 mg / L; Nitrate (NO3) from 0.003 to 0.1593 mg / L; Nitrite (NO2) 0.001 - 0.0085 mg / L; Phosphate (PO4) 0.045 to 0.198 mg / L; Iron (Fe) 0.035 to 0.652 mg / L; and Total Suspendet Solit (TSS) 34-125 mg / L. The potential for seaweed cultivation of 17,391.87 hectares of land in accordance with the level of compliance and inappropriate 9,858.62 7,533.25 ha ha, whereas eksisiting 9,614.42 ha of land.